From local monitoring to a broad‐scale viability assessment: a case study for the Bonelli's Eagle in western Europe. Issue 2 (1st May 2013) - Hernández-Matías, Antonio; Real, Joan; Moleón, Marcos; Palma, Luis; Sánchez-Zapata, Jose Antonio; Pradel, Roger; Carrete, Martina; Gil-Sánchez, Jose María; Beja, Pedro; Balbontín, Javier; Vincent-Martin, Nicolas; Ravayrol, Alain; et al.
Abstract : Population viability analysis (PVA) has become a basic tool of current conservation practice. However, if not accounted for properly, the uncertainties inherent to PVA predictions can decrease the reliability of this type of analysis. In the present study, we performed a PVA of the whole western European population (France, Portugal, and Spain) of the endangered Bonelli's Eagle ( Aquila fasciata ), in which we thoroughly explored the consequences of uncertainty in population processes and parameters on PVA predictions. First, we estimated key vital rates (survival, fertility, recruitment, and dispersal rates) using monitoring, ringing, and bibliographic data from the period 1990–2009 from 12 populations found throughout the studied geographic range. Second, we evaluated the uncertainty about model structure (i.e., the assumed processes that govern individual fates and population dynamics) by comparing the observed growth rates of the studied populations with model predictions for the same period. Third, using the model structures suggested in the previous step, we assessed the viability of both the local populations and the overall population. Finally, we analyzed the effects of model and parameter uncertainty on PVA predictions. Our results strongly support the idea that all local populations in western Europe belong to a single, spatially structured population operating as a source–sink system, whereby the populations in the south of the Iberian Peninsula act as sources and, thanks to dispersal, sustain all other local populations, which would otherwise decline. Predictions regarding population dynamics varied considerably, and models assuming more constrained dispersal predicted more pessimistic population trends than models assuming greater dispersal. Model predictions accounting for parameter uncertainty revealed a marked increase in the risk of population declines over the next 50 years. Sensitivity analyses indicated that adult and pre‐adult survival are the chief vital rates regulating these populations, and thus, the conservation efforts aimed at improving these survival rates should be strengthened in order to guarantee the long‐term viability of the European populations of this endangered species. Overall, the study provides a framework for the implementation of multi‐site PVAs and highlights the importance of dispersal processes in shaping the population dynamics of long‐lived birds distributed across heterogeneous landscapes.